Rachunek rezultatów jako instrument controllingu zasobów ludzkich w urzędzie gminy - Bednarek, Piotr (Activity Accounting as a Tool Of Human Resources Controllership In Local Government Office, 2008)
Human resources management is very important in every organization. However for service providers like local government office, it seems to be essential if they want to operate in a cost-effective manner. This paper shows that activity accounting can be a useful tool for controller who is responsible for delivering information for management on how efficient and effective are the workers in each responsibility center. Moreover it presents how this data can be used in order to improve performance of local government office.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 20-32